Clinical impact of monitoring frequency per day as a prospective audit and feedback strategy for patients receiving antimicrobial agents by injection. Issue 11 (14th September 2021) - Goto‐Fujibayashi, Ayasa; Niwa, Takashi; Yonetamari, Jun; Ito‐Takeichi, Syuri; Suzuki, Keiko; Ohta, Hirotoshi; Niwa, Ayumi; Tsuchiya, Mayumi; Ito, Yukiko; Hatakeyama, Daijiro; Hayashi, Hideki; Sugiyama, Tadashi; et al.
Abstract: Background: Implementation of antimicrobial stewardship programmes improve antimicrobial therapies and thus result in better patient outcomes and safety. The impact of prospective audit and feedback (PAF) is likely dependent on how frequently it is conducted, and how quickly after antibiotic prescription it is initiated. To our knowledge, however, no report has yet investigated the impact of an increase in monitoring frequency per day on PAF strategy. Here, we evaluated the clinical impact of an increase in monitoring frequency per day as a PAF strategy in patients receiving antimicrobial injections. Methods: We conducted a single‐centre, retrospective observational pre‐post study to evaluate the impact of increasing the frequency of monitoring from once daily (once daily review group) to twice daily (twice daily review group). Time to intervention and clinical outcomes were compared before and after implementation of twice daily review. Results: Time to intervention for inappropriate antimicrobial therapy was significantly shorter in the twice daily review group than the once daily review group (5.1 ± 6.1 hours vs 29.9 ± 21.5 hours, HR: 4.53, 95% CI: 2.90‐7.07, P  < .001). The twice daily review group had a significantly lower rate of clinical failure (16.2% vs 38.3%, P  = .004) and hepatotoxicity (4.1% vs 15.0%, P  = .035) than the once daily review group. Conclusions: An increase in monitoring frequency from once daily to twice daily significantly shortened the time to intervention for inappropriate antimicrobial therapy, with a concomitant reduction in clinical failure and hepatotoxicity.